Movement, activity, and landscape use patterns of heritage and commercial beef cows grazing Chihuahuan Desert rangeland. (April 2022) - Nyamuryekung'e, Shelemia; Cibils, Andres F.; Estell, Richard E.; VanLeeuwen, Dawn; Spiegal, Sheri; Steele, Caitriana; González, Alfredo L.; McIntosh, Matthew M.; Gong, Qixu; Cao, Huiping
Abstract: The objective of this study was to compare foraging behavior of mature Raramuri Criollo (RC, heritage breed) and Angus Hereford crossbred (AH, commercial breed) cows grazing Chihuahuan Desert rangeland during summer and winter in three consecutive years. Movement, activity, and spatial distribution variables were calculated from 10-min interval GPS positions of 5–11 randomly selected cows of each breed. Thirteen pasture pixel attributes were used to analyze grazing utilization and selection patterns of both breeds. Statistical mixed models were used to determine the effects of breed and season on all foraging response variables. Spatial regression analysis was used to examine resource utilization. Compared to AH, RC cows traveled farther at higher velocity rates, spent less time resting, more time grazing and traveling, explored larger areas as individuals, and exhibited lower herd cohesion. The RC herd explored more grazing patches (30-m pixel) overall and exhibited lower patch residence times in winter, a foraging strategy linked with lighter environmental footprint. During summer, similar pixel variables explained re-visitation rates of cows of both breeds. Both breeds avoided areas far from water, but RC cows showed higher avoidance of pixels farther out from a drinker during the dormant season. RC cows appeared to exhibit a keener ability to select patches with differing surface temperature, and greenness compared to AH counterparts. RC cows showed higher preference for pixels with high shrub density than AH counterparts in summer. During the dormant season, AH cows exhibited a strong preference for black grama patches, a species with high ecological value, and higher avoidance of patches with high density of other grasses. Differences in foraging behavior documented in this study support the hypothesis that RC cattle could impose a lighter footprint on desert rangeland relative to commonly raised commercial beef cattle. Highlights: Raramuri Criollo cows (heritage breed) exhibited more desirable spatial distribution patterns (traveled farther, spent more time grazing and traveling, and explored larger areas of the pasture) than commercial beef breed counterparts. Breed differences in resource selection and utilization were largest during the dormant season. Raramuri Criollo (heritage breed) could have a lighter footprint on desert rangeland compared to Angus Hereford crossbred (commercial breed) cattle.